Does Liposuction Improve Body Image and Symptoms of Eating Disorders? - Saariniemi, Kai M. M. (Plast Reconstr Surg Glob Open, 2015)
BACKGROUND: Unpleasant attention to unfavorable fat may have harmful psychological effects in terms of body dissatisfaction. As a consequence, this may cause abnormal eating regulation. It has been noted that women interested in liposuction self-report more eating problems. As far as we know, there are no prospective studies with standardized instruments providing sufficient data regarding the effects of aesthetic liposuction on various aspects of quality of life. Nevertheless, publications on the effects of eating habits are lacking. METHODS: Sixty-one consecutive women underwent aesthetic liposuction. Three outcome measures were applied at baseline and at follow-up: the eating disorder inventory, Raitasalo's modification of the Beck depression inventory, and the 15-dimensional general quality of life questionnaire. RESULTS: The mean age at baseline was 44 years, and the mean body mass index was 26.0. Thirty-six (59%) women completed all outcome measures with a mean follow-up time of 7 months. A significant improvement from baseline to follow-up was noted in women's body satisfaction, and their overall risk for developing an eating disorder decreased significantly. CONCLUSION: Aesthetic liposuction results in a significantly reduced overall risk for an eating disorder in combination with improved body satisfaction.